PENDEKATAN SAINTIFIK EFEKTIF DALAM PEMBELAJARAN DI SEKOLAH DASAR - Fransiska Jaiman Madu; Marlinda Mulu; Mariana Jediut; Zephisius Rudiyanto Eso Ntelok; Rudolof Ngalu (PGSD UNIKA SANTU PAULUS RUTENG, 2021)
Application of Scientific Approach in Primary Schools. The rationale for this research is the discovery of problems related to the low ability of students to present report texts based on observations. based on these problems offered a solution that is the use of a scientific approach, which approach has a characteristic that is a series of processes or stages in learning that must be passed by students. the use of this approach is considered effective to provide solutions to the problems encountered. This approach was chosen because of the recommendations of previous studies. The purpose of this study is to describe the effectiveness of the use of scientific approaches in elementary schools. this type of research is qualitative with descriptive methods. The results showed that the use of a scientific approach in learning can be said to be effective. This can be seen in students' progress in preparing reports based on observations. in addition, students follow well the stages of the scientific approach in learning.